Doctor Appointment Checklist - Martie Gillen; Carolyn S. Wilken (EDIS, 2012)
When you have a doctor appointment, you should make the most of your time with the doctor. This worksheet will help you remember what questions you want to ask and give you a space to take notes. This document is also beneficial if you are a caregiver for an older adult and go along to appointments. This revised 5-page fact sheet was written by Martie Gillen and Carolyn S. Wilken, and published by the UF Department of Family, Youth and Community Sciences, August 2012.